INDUSTRIAL TYPES OF CARBONATE RAW MATERIAL DEPOSITS AND THEIR CUT OFF PARAMETERS FOR RESERVES ESTIMATION - Mayboroda, Ye.; Kurylo М. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article systematizes the main industrial types of carbonate rock deposits in Ukraine and analyzes the main directions of their use. Metallurgical production and the sugar industry are identified as the main areas of use that are in short supply. Most of these explored reserves of carbonate rocks are located within the Donetsk region and the territory of Crimea. The number of explored reserves in the rest of the territory does not provide a sufficient period of operation and work of industrial enterprises for more than 10-15 years. The most effective way to provide reserves is to review the objects that are being developed today in other areas of use (except metallurgical raw materials and the sugar industry) to allocate a part of the reserves that may be suitable for these scarce areas.The analysis and systematization of the cut-off parameters for the reserves calculation of various types of carbonate rocks in accordance with their industrial types and the requirements of geological and economic evaluation were carried out. The basic parameters for the calculation of reserves are the quality indexes, which are put forward by the direction of use in the standards, the depth of the reserves calculation, the minimum thickness of the mineral from 2 m, the limitation of contours within the license area and the mining right-of-way, in the contour of the quarry at the end of the development. Parameters that take into account the risks of unconfirmed reserves associated with karst areas, high clayey rocks are almost not used, although they can be an important tool especially for operational conditions.